Gestión emocional en estudiantes de Instituciones Educativas de Riobamba - Maldonado Lalama, Paola Sofía (2025)
This research addresses the impact of emotions and their management in education, given their great importance in personal, social, and academic contexts. Therefore, the objective is to establish how students from UEPAIS and the “Fe y Alegría” Basic Education School manage their emotions. Based on the foundations established by Cano and Zea regarding emotional management, it is defined as understanding how emotions manifest in individuals to find ways to address each one, guiding our behavior according to our emotional state. Regarding the methodology, the research was conducted using a qualitative approach, a non-experimental and descriptive design, and a cross-sectional study with a total sample of 56 students from both educational institutions where the research was carried out. The technique used was the survey, and the instrument was a questionnaire developed by the researcher. This research aims to contribute knowledge about the importance of emotional education in classrooms and to promote greater participation of the entire educational community in managing emotions. The goal is to provide society with emotionally stable individuals capable of facing adversities with appropriate strategies.